2008
DOI: 10.1071/ar06325
|View full text |Cite
|
Sign up to set email alerts
|

Are temperature effects on weight and quality of barley grains modified by resource availability?

Abstract: Under field conditions the occurrence of brief periods of moderately high (30–32°C) and very high temperatures (>35°C) is quite common during grain filling in small-grain cereals. These events occur under a wide range of different management and environmental conditions, such as different nitrogen supplies and source–sink ratios after flowering. The objective of the present work was to study whether the effect of a brief heat stress is modified by resource availability for the growing grains. We subjected s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 34 publications
3
13
1
Order By: Relevance
“…High temperature during pre-anthesis period in season 2003 decreased the final number of tillers (Pržulj and Momčilović 2012), which is in agreement with the results of Garcia del Moral et al (2003). Besides negative effects on barley grain yield, high temperatures and drought stress increased protein concentration in barley grain (data not shown), which is in negative correlation with malt quality (Passarella et al 2008). In contrast to year 2003,2001 was characterized by high average grain yield and favourable climate for barley growth.…”
Section: Discussionsupporting
confidence: 80%
“…High temperature during pre-anthesis period in season 2003 decreased the final number of tillers (Pržulj and Momčilović 2012), which is in agreement with the results of Garcia del Moral et al (2003). Besides negative effects on barley grain yield, high temperatures and drought stress increased protein concentration in barley grain (data not shown), which is in negative correlation with malt quality (Passarella et al 2008). In contrast to year 2003,2001 was characterized by high average grain yield and favourable climate for barley growth.…”
Section: Discussionsupporting
confidence: 80%
“…Yield improvement in temperate maize is attributed to greater high temperature stress tolerance, N uptake and associated N efficiency. However, these results were, in contrast to previous reports that observed that sensitivity of yield to heat stress, increased with the level of N availability in wheat (Altenbach et al 2003, Zahedi et al 2004, in barley (Passarella et al 2008) and in maize (Ordóñez et al 2015). On the one hand, these previous studies were conducted under more or less controlled environments which therefore extended the magnitude of HTS (for example, the maximum air temperature in Ordonez's experiment exceeded 40°C, which rarely appeared in field conditions).…”
Section: Resultscontrasting
confidence: 54%
“…Field experiments on wheat showed that the degree of damage under HTS increased with higher nitrogen availability, consequently resulting in a reduction in final yield (Morris et al 2006). However, several investigations demonstrated that sensitivity of crop yield to heat stress was increased with nitrogen fertilization in wheat (Altenbach et al 2003, Zahedi et al 2004, in barley (Passarella et al 2008) and in maize (Ordóñez et al 2015). Maize will be more often subject to HTS in the context of climate changes.…”
mentioning
confidence: 99%
“…Both in wheat (Altenbach et al, 2003;Zahedi et al, 2004) and in barley (Passarella et al, 2008) it has been shown that the penalty on yield imposed by exposure to high temperatures were affected by the level of N availability: the higher the availability the more damaging the high-temperature effect (Altenbach et al, 2003;Zahedi et al, 2004;Passarella et al, 2008). Although the mechanisms involved are not understood, reporting evidences of this type of interaction would be relevant in practical terms.…”
Section: Introductionmentioning
confidence: 91%